1979
DOI: 10.1017/s0021859600062791
|View full text |Cite
|
Sign up to set email alerts
|

Digesta flow and mineral absorption in lambs before and after weaning

Abstract: Four young lambs fitted with cannulas at the pylorus and at the ileo-caecal junction were used to study the effects of weaning on digesta flow and mineral absorption. Prior to weaning when milk alone was fed the small intestine was the major site for dry matter disappearance and for the absorption of Ca, P, Na and K. Both the small and the large intestine were, however, important sites for Mg absorption at this time.After weaning, when the lambs were fed a concentrate diet, at least two-thirds of the digested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

1980
1980
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 15 publications
1
5
0
1
Order By: Relevance
“…The major role of the small intestine in P and Ca absorption, and that of the stomach in Mg absorption, has been demonstrated and confirmed in many studies with sheep (Ben-Ghedalia et al 1975;Tomas & Potter, 1976;Dillon & Scott, 1979). The data of the present study show that the absorption sites of Ca, P and Mg in sheep fod a PL-supplemented diet are the same as those found with conventional sources of the elements.…”
Section: Discussionsupporting
confidence: 85%
“…The major role of the small intestine in P and Ca absorption, and that of the stomach in Mg absorption, has been demonstrated and confirmed in many studies with sheep (Ben-Ghedalia et al 1975;Tomas & Potter, 1976;Dillon & Scott, 1979). The data of the present study show that the absorption sites of Ca, P and Mg in sheep fod a PL-supplemented diet are the same as those found with conventional sources of the elements.…”
Section: Discussionsupporting
confidence: 85%
“…It can be concluded that the RU is a main site for active Ca transport mechanisms in growing goat kids. Previous studies described Ca net absorption before the DD in single-and multi-fistulated ruminants ( Pfeffer et al, 1970;Dillon and Scott, 1979;Wylie et al, 1985). Höller et al (1988) and Schröder et al (1997Schröder et al ( , 1998) also observed active Ca transport mechanisms in caprine and ovine rumen by Ussing chamber technique.…”
Section: Discussionmentioning
confidence: 96%
“…It is not known, how the ruminal Ca absorption influences Ca homoestasis (Martens, 2005). Different studies showed different results on the permeability of Ca across ruminal epithelium (Pfeffer et al, 1970;Dillon and Scott, 1979;Schröder et al, 1995;2001).…”
Section: Introductionmentioning
confidence: 99%
“…In balance experiments with sheep cannulated in the proximal duodenum or supplied with fistulae in the abomasum and fed between 2 and 18 g calcium/day, Ca2+ movement through the pre-duodenal part of the gastrointestinal tract was measured by several authors. Ca2+ net secretion into the tract in the range between 0.15 and 1-44 g/day was found by Pfeffer, Thompson & Armstrong (1970), Ben-Ghedalia, Tagari, Zamwel & Bondi (1975), Greene, Webb & Fontenot (1983) and Wylie, Fontenot & Greene (1985), Ca2+ net absorption from the upper part of the tract of between 0 5 and 4-3 g/day was observed by Grace, Ulyatt & MacRae (1974), Leibholz (1974), Dillon & Scott (1979), Breves (1985) and Grings & Males (1987), whereas no Ca2+ net movement across the walls of this region was detected by Pfeffer (1968) and Sklan & Hurwitz (1985). It should be noted, however, that all balance data cited above included endogenous Ca2+ inflow with saliva which should amount to 0 2-0 3 g/day (Rosenhagen, 1985) and also some addition of Ca2l with gastric juice.…”
Section: Introductionmentioning
confidence: 82%